The Impact of a Health Information Technology–Focused Patient-centered Medical Neighborhood Program Among Medicare Beneficiaries in Primary Care Practices: The Effect on Patient Outcomes and Spending. Issue 4 (April 2018) - Orzol, Sean; Keith, Rosalind; Hossain, Mynti; Barna, Michael; Peterson, G. Greg; Day, Timothy; Gilman, Boyd; Blue, Laura; Kranker, Keith; Stewart, Kate A.; Hoag, Sheila; Moreno, Lorenzo
Abstract : Background: The Center for Medicare & Medicaid Innovation (CMMI) tests new models of paying for or delivering health care services and expands models that improve health outcomes while lowering medical spending. CMMI gave TransforMED, a national learning and dissemination contractor, a 3-year Health Care Innovation Award (HCIA) to integrate health information technology systems into physician practices. This paper estimates impacts of TransforMED's HCIA-funded program on patient outcomes and Medicare parts A and B spending. Research Design: We compared outcomes for Medicare fee-for-service (FFS) beneficiaries served by 87 treatment practices to outcomes for Medicare FFS beneficiaries served by 286 matched comparison practices, adjusting for differences in outcomes between the 2 groups during a 1-year baseline period. We estimated impacts in 3 evaluation outcome domains: quality-of-care processes, service use, and spending. Results: We estimated the program led to a 7.1% reduction in inpatient admissions and a 5.7% decrease in the outpatient emergency department visits. However, there was no evidence of statistically significant effects in outcomes in either the quality-of-care processes or spending domains. Conclusions: These results indicate that TransforMED's program reduced service use for Medicare FFS beneficiaries, but also show that the program did not have statistically significant favorable impacts in the quality-of-care processes or spending domains. These results suggest that providing practices with population health management and cost-reporting software—along with technical assistance for how to use them—can complement practices' own patient-centered medical home transformation efforts and add meaningfully to their impacts on service use. Abstract : Supplemental Digital Content is available in the text.